The University Degree in Environment and workplace prevention techniques: a quasi unicum Course in the European panorama for non-medical professionals involved in prevention activities - Bizzarro, Assunta; Rossi, Deanna; Zoni, Roberta; Affanni, Paola; Mazzocchi, Barbara; Pasquarella, Cesira; Goldoni, Matteo; Romanò, Luisa; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
The University Degree programme in Environment and workplace prevention techniques (Tecniche della Prevenzione nell’Ambiente e nei Luoghi di Lavoro) is a 3-year course established in Italy in 2000 by the Ministry of University to train healthcare professionals responsible for prevention activities such as environment and food controls, and workplaces prevention, operating both in the National Health Service and in private settings. Frontal teaching activities and training programmes include a background in bio-medical sciences, epidemiology, public health, social sciences and law, including the inspection and control tasks of health and safety in living and working environment, food hygiene, environmental controls and veterinary public health, which represent the field of specific competences of graduates. Currently, 38 courses have been activated in 30 Italian Universities, but relatively few similar courses are present in Europe (similar programmes were found in France, Spain, UK and Belgium) causing the lack of internalization and student exchange programmes. It is essential to identify similar training tasks in other European countries, in order to enhance cultural exchanges and the development of research activities in these strategic areas.